Answer:Side x side x side
Step-by-step explanation:
Since it is usually equally sided, it would be SxSxS
The function f(x) is defined in to different ways depending on the value of X. When x is < 5, use the expression 2x - 1 to evaluate the function When x is ≥ 5, use the expression x2 - 3 for example f(1) = 2(1) - 1 = 1 f(10) = (10)2 - 3 = 97
Answer:
x³ + 7x² - 6x - 72
Step-by-step explanation:
Given
(x + 6)(x + 4)(x - 3) ← expand the second and third factor, that is
(x + 4)(x - 3)
Each term in the second factor is multiplied by each term in the first factor, that is
x(x - 3) + 4(x - 3) ← distribute both parenthesis
= x² - 3x + 4x - 12 ← collect like terms
= x² + x - 12
Now multiply this by (x + 6) in the same way
(x + 6)(x² + x - 12)
= x(x² + x - 12) + 6(x² + x - 12) ← distribute both parenthesis
= x³ + x² - 12x + 6x² + 6x - 72 ← collect like terms
= x³ + 7x² - 6x - 72
Answer:
g(x)
because it is a quadratic equation it is mirrored the other one isn’t even a function